Muli Mekhanai Sekuakhian Paradigm as Ta'aruf Method in Lampung Pepadun Indigenous People in Maqashid Al-Shari'ah - Agus Hermanto; Rudi Santoso; Rochmad; Rita Zaharah (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
Sekuakhian activities are customary of the Lampung Pepadun community as a method to choose potential partners that have been carried out by their predecessors. However, with the development of people's lifestyles, so that this activity often causes different sites from previous habits, therefore, it is interesting to study in depth the socio-philosophy of this custom, in order to get its true meaning. The problem is how to implement the customary sekuakhian muli mekhanai in the review of maqashid al-shari'ah? The purpose of this study is to examine in depth the paradigm of the indigenous people of Lampung Pepadun in the sekuakhian muli mekhanai in the review of maqashid al-shari'ah. This research is in the form of qualitative field research taken from primary data taken from indigenous people of Lampung Pepadun, while the skunder data is from the results of written works both books, journals and other articles related to the Lampung Pepadung custom, especially about sekuakhian customs.The result of this study is that the paradigm of the indigenous people of Lampung Pepadun about the sekuakhian muli mekhanai is a method for choosing a life partner, which if viewed in the study of maqasid al-shari'ah philosophically does not actually contradict the law of shari'a, but because this activity then underwent a paradigm shift, until then there were several things that plunged into things that led to the action that forbidden by religion.